Quantifying hydrothermal alteration Derived by remote sensing technique in Tompaso Geothermal Field (North Sulawesi Indonesia) - Bariadi, Laode; Saepuloh, Asep (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
Quantifying hydrothermal alteration is important for geothermal system modeling, which aims to understand fluid dynamics, soil distribution, and energy production potential in the geothermal exploration areas as well as the economic mineral potential at the Tompaso area, North Sulawesi. Alteration processes can result in weathering degradation of rock strength. The Sentinel-2 color composite of band ratio R,G,B for band (4/2), band (8A/11), and band (11/12) reveals the distribution of iron oxides, ferromagnesian silicates, and clay minerals. These alteration minerals are characterized by the presence of clay minerals such as chlorite (Chl), epidote (Ep), quartz (Qs), sericite (Sr), alunite (Al), and illite (ill), which formed at temperatures of 110-300⁰C and fluid pH ranging from 3-5 (acidic in nature). The process of geological phenomena in the form of structures that open fluid pathways affects changes in the physical and chemical composition of the host rocks. The host rock and hydrothermal interactions influence to the fertility as well as vegetation conditions. Therefore, the soil and vegetation conditions were used to trace the occurrence of hydrothermal alteration minerals. A band ratio of the chlorophyll spectrum captured by the red edge vegetation index (REVI) is used as a basis for mapping vegetation stress related to the occurrence of the alteration minerals. The insitu chlorophyll measurements of ferns were used to verify the REVI in the study area. The REVI image shows anomalous vegetation stress corresponding to alteration minerals. To quantify the detection correctness, the SPAD soil measurements were conducted to pinpoint vegetation stress caused by the existence of hydrothermal alteration minerals. Correlation between alteration minerals to these two variables REVI and fern SPAD. The determination coefficient (R2) between REVI and alteration minerals then the alteration minerals and SPAD chlorophyll measurements were archived linearly about 0.7. We have also obtained a linear correlation with positively gradient between alteration zones of argillic and propylitic presented by occurrences of kaolinite, sericite, chlorite, epidote, and quartz minerals in rock samples, to stressed vegetations.